INSURANCE RELATIONSHIPS ORGANIZE REACH FORMS - Tugizova Malika Sokhib kizi (American Journals, 2023)
Classification all joints insurance done increase forms cover takes mandatory and optional of the parties at will according to done to be increased insurance optional insurance is considered. Optional insure conditions of the parties agreement basically is determined. Rights and obligations of the insured and the insurer, as well as each insurance of type sure conditions belongs to insurance contracts with set is poured.
Keywords: voluntary insurance, demand reflection, liability insurance, mandatory insurance.